Geochemical characteristics of the Paleozoic natural gas in the Yichuan-Huanglong area, southeastern margin of the Ordos Basin: Based on late gas generation mechanisms. (February 2021) - Feng, Ziqi; Dong, Dazhong; Tian, Jinqiang; Zhou, Shangwen; Wu, Wei; Xie, Chen
Abstract: As a new expansion area for natural gas exploration, the Yichuan-Huanglong area improves the complete evolutionary sequence of the Paleozoic natural gas in the eastern part of the Ordos Basin, but the geochemical characteristics and the late gas generation processes involved have not been discussed. By collecting and analyzing gas samples from existing wells, the following insights were obtained. The alkane components had a dichotic characteristic, the wetness of the O1 m5 –C2 b natural gas (average: 3.85%) was relatively higher than that of the Permian natural gas (average: 0.88%). The carbon isotopic compositions exhibited partial reversal (δ 13 C-CH4 >δ 13 C-C2H6 ), and the Permian natural gas from the coal-measure strata had abnormally low δ 13 C-C2H6 values (<−28‰). The O1 m5 –C2 b natural gas had characteristics typical of oil-associated gas, whereas the Permian natural gas had the mixed characteristics of coal-derived gas and oil-associated gas. The mixing and diffusion effects illuminated the isotopic anomalies of the alkane gas. According to the source rocks and the thermal maturity, mechanisms such as the depletion of 13 C in the residual ethane, water-reforming, and the Fischer-Tropsch-like mechanism, and the demethylation of aromatic hydrocarbons also provided important information about the late gas generation of the Paleozoic natural gas in the Yichuan-Huanglong area. Highlights: First research on the geochemical characteristics of the Paleozoic natural gas in the study area. The mixing and diffusion effects illuminate the isotopic anomalies of the alkane gas. The mechanisms that may occur during late gas generation are discussed systematically.